2014
DOI: 10.1371/journal.pone.0102504
|View full text |Cite
|
Sign up to set email alerts
|

True Zero-Training Brain-Computer Interfacing – An Online Study

Abstract: Despite several approaches to realize subject-to-subject transfer of pre-trained classifiers, the full performance of a Brain-Computer Interface (BCI) for a novel user can only be reached by presenting the BCI system with data from the novel user. In typical state-of-the-art BCI systems with a supervised classifier, the labeled data is collected during a calibration recording, in which the user is asked to perform a specific task. Based on the known labels of this recording, the BCI's classifier can learn to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 36 publications
0
62
0
Order By: Relevance
“…The performance, however, drops considerably when moving out of the lab and into end users’ homes [49]. Some studies have shown EP-based BCIs that yield good performance with subject-independent classifiers, i.e., without calibration at all for a new user [78, 79]. However, so far these approaches have mainly been tested in offline studies and with healthy users only.…”
Section: Signal Processing and Decodingmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance, however, drops considerably when moving out of the lab and into end users’ homes [49]. Some studies have shown EP-based BCIs that yield good performance with subject-independent classifiers, i.e., without calibration at all for a new user [78, 79]. However, so far these approaches have mainly been tested in offline studies and with healthy users only.…”
Section: Signal Processing and Decodingmentioning
confidence: 99%
“…It is therefore still unknown whether this results generalize to end-users. Moreover, performances are still better when exploiting subject-specific data and user training, even for P300-based BCI [79, 80]. …”
Section: Signal Processing and Decodingmentioning
confidence: 99%
“…The ability to use a BCI without calibration or after a short calibration has been recognized in the community as a priority for improving BCI usability. Toward this objective effort is put in the conception, analysis and testing of generic model classifiers and/or domain adaptation methods, allowing the so-called transfer learning, whereas data from other sessions and/or other subjects are used to initialize a BCI so as to start using it without calibration and also to increase the performance of low-performance users [25,30,[57][58][59][60][61][62][63].…”
Section: Bci Decoders Of Second Generationmentioning
confidence: 99%
“…It also allows keeping optimal performance by adapting to mental and environmental changes during the session, enabling continuous adjustments ("pursuing"), thus ensuring reliability and robustness throughout the session and across-sessions [30,62,[64][65][66].…”
Section: The Continuous (On-line) Adaptation Of the Classifier Whichmentioning
confidence: 99%
“…Auto-calibration procedures allow expert-independent home-use of a BCI as they allow people with no technical knowledge to set up the system. Though such calibration methods are common for other BCI approaches [10,13,15,16], they are rarely used for BCIs based on the SSVEP paradigm. However, in the here presented dictionary supported SSVEP-based BCI, a modified version of our earlier developed calibration methods [9] was integrated to set up user specific stimulation frequencies and other key parameters associated with the utilized classification methods such as frequency dependent classification thresholds.…”
mentioning
confidence: 99%